IMPLEMENTASI METODE PEMBELAJARAN LOOSE PART DALAM MENGEMBANGKAN KREATIVITAS ANAK USIA DINI - Nafisa Zakiyah; Riris Prasetyawati; Theresa Luvita Yani (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Implementation Of Loose Part Learning Methods In Developing Creativity In Early Children. Early childhood has a creative nature. Children's creativity can be developed with play activities that are appropriate for the child's age. One method that can increase the creativity of early childhood is the loose part method. The learning method uses loose parts, namely by using natural materials around the house that can be reused in the creativity of early childhood. The research used is descriptive qualitative method. The subjects of this study were school principals, group B teachers and group B children at Kindergarten Dharma Indria I. The data were collected using interviews, observation and documentation using data analysis using interactive models. The loose parts method applied in Kindergarten Dharma Indria 1 gives children the freedom to explore the environment directly and can enrich ideas and creative imagination. Starting with media planning and loose part materials prior to learning activities, carrying out activities with children imagining their own work using the tools provided. Children's creativity can be seen when children choose materials and can also be seen from the work they produce. Furthermore, the teacher evaluates learning using loss part materials